NEED ANALYSIS FOR THE DEVELOPING OF DIGITAL LEARNING MODULE INTEGRATED DISASTER LITERACY FOR CLASS VII JUNIOR HIGH SCHOOL - Rilla Yulistika (Pendidikan IPA, FMIPA, UNP, 2022)
Integrated science learning about disaster knowledge is one approach in the disaster mitigation education program. Howefer, One of the efforts that can be done is to integrate disaster mitigation knowledge into science teaching materials. This describtive is an preliminary research of Research and Development (R&D) research. This study aims to describe the need to develop integrated digital teaching materials for disaster literacy for science students. The data instruments used in this study were interview sheets and questionnaires. Data anaiyzed describtively use percentage. Research result informed that less than 50 percent of junior high school students are still not familiar with the term disaster mitigation, and there is no digital module available in the junior high schools studied.